Legal protection for justice collaborators in premeditated murder from a human rights perspective - Sulasri Waruwu; Rini Melda Laia; Khomaini Khomaini (Institute Of computer Science (IOCS), 2024)
The crime of premeditated murder is one of the serious or extraordinary crimes (Extra Ordinary Crime) which tends to be difficult to uncover. Therefore, the idea of a witness who cooperates with the perpetrator (Justice Collaborator) emerged. The purpose of this research is to find out the legal provisions on the status of Justice collaborators in providing testimony in cases of premeditated criminal acts, to find out the role of justice collaborators in providing testimony, then the form of legal protection against the status of justice collaborators. This research method uses the type of normative legal research, with data collection used in this research includes library research. According to the researcher's analysis, the form of legal protection of Justice Collaborator is still no regulation that regulates specifically, clearly and firmly regarding the regulation and procedural determination as a Justice Collaborator, the rules regarding the protection of Justice Collaborator should be regulated in detail and clearly because the role of witnesses who cooperate is needed to uncover cases that tend to be difficult to uncover. his testimony can pose a great risk that must be borne by the Justice Collaborator. Legal protection of Justice Collaborators is a very urgent matter, especially when viewed from a Human Rights perspective.